Sony Ericsson / Anna Aidette Jiman ... [et al.] - Jiman, Anna Aidette; Alister Australia, Cathryn Leigh; Mathew, Denise; David, Irene; Berasap, Lorita Mihiba (2016)
Sony Ericsson was formed by Ericsson and Sony in 2001. In just a few years, Ericsson hand phone managed to become popular and successful around the whole world. . Ericsson then had begun to experience technical problems with its hand phones. Some of the problems are lack of back-up systems and the lack of skills with consumer products. On 24th April 2001, Ericsson mobile phones operate together with Sony's Japan to form Sony Ericsson. In January 2012, Sony possessed Ericsson's stake for $ 1.47 billion which makes the mobile handset business folly owned by Sony. Sony mobile is owned by Sony Corporation. It was founded in May 7, 1946. The present CEO of the Sony Corporation is Kazuo Hirar. It was headquartered at Tokyo, Japan and the name Sony is based on the Latin word Sonus, which means 'sound'. Sony Corporation is the holding company as it is a parent company of Sony group. Sony are also leading the Japanese manufacturer of electronics, games and entertainment products. Apart from that, Sony Corporation is also engaged in the financial services businesses. In the year end of March 2012, Sony Corporation announced a record annual net loss of 520 billion yen (£6.4 billion) and in the last few years, Sony has been losing money. This is due to the fierce increased in competition between Apple Inc. and Samsung Electronics Inc. After the loss of the Sony Corporation, they set the main goals which are continuing in promoting technological innovations and product developments that will help in contributing to the cultural and social progress.